2001
DOI: 10.4049/jimmunol.167.5.2608
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-12 p40 Promoter Activity in Primary Human Monocytes: Roles of NF-κB, CCAAT/Enhancer-Binding Protein β, and PU.1 and Identification of a Novel Repressor Element (GA-12) That Responds to IL-4 and Prostaglandin E2

Abstract: Appropriate regulation of IL-12 expression is critical for cell-mediated immune responses. In the present study, we have analyzed the regulation of IL-12 p40 promoter activity in primary human monocytes in vivo. Accordingly, we analyzed the p40 promoter by in vivo footprinting in resting and activated primary human blood CD14+ monocytes. Interestingly, footprints at binding sites for trans-activating proteins such as C/EBP, NF-κB, and ETS were only found upon stimulation with LPS and IFN-γ. In contrast, a foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 55 publications
(39 reference statements)
2
80
1
Order By: Relevance
“…Conversely, mutagenesis of the AP-1 site alone in this IL-12p40 promoter construct failed to abrogate luciferase activity (data not shown). These results are contrary to the observations provided by Becker et al (25) whereby mutations of NF-B, Ets, and C/EBP sites reduced IL-12p40 promoter activity even though the AP-1 site was left intact. Although the reasons for this discrepancy are not clear, it appears that IL-12p40 gene transcription may be subject to differential regulation depending on the cell type and the nature of the external stimuli used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely, mutagenesis of the AP-1 site alone in this IL-12p40 promoter construct failed to abrogate luciferase activity (data not shown). These results are contrary to the observations provided by Becker et al (25) whereby mutations of NF-B, Ets, and C/EBP sites reduced IL-12p40 promoter activity even though the AP-1 site was left intact. Although the reasons for this discrepancy are not clear, it appears that IL-12p40 gene transcription may be subject to differential regulation depending on the cell type and the nature of the external stimuli used.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Ma et al (22,23) demonstrated the role of the Ets-2 transcription factor in stimulation of human IL-12p40 (hIL-12p40) promoter in IFN-␥-and LPS-stimulated murine RAW264 monocytic cells. Recently, several other studies have reported the involvement of IFN-␥ regulatory factors, NF-B, Ets-2, and PU.1 transcription factors in IL12p40 regulation (25,27).…”
mentioning
confidence: 99%
“…The interaction between IRF-8 and IRF-1, both of which are IFN-␥-inducible, together with PU.1, which is an hematopoietic specific factor expressed constitutively in these cells, is a paradigm for the expression of many genes in mature macrophages like the phagocytic oxidase subunits (p67 and gp91) (44), IL-1␤ (45), ISG15 (32), Nramp1 (31), , and IL-12 (47,48). This complex is therefore characteristic of enhanceosomes of many IFN-␥ induced genes in mature macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…GAP-12, to the GATA sequence (GA-12) in the IL-12p40 promoter has been shown to repress IL-12p40 promoter activity (37,38). To determine the role of GAP-12 in GPI-induced IL-12 regulation, EMSA was performed using a DNA probe containing the GATA sequence (GA-12) of the IL-12p40 promoter.…”
Section: Macrophages Upon Stimulation Of Mk2mentioning
confidence: 99%